If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(3x + -2) = (3x + 1)(x + -2) Reorder the terms: x(-2 + 3x) = (3x + 1)(x + -2) (-2 * x + 3x * x) = (3x + 1)(x + -2) (-2x + 3x2) = (3x + 1)(x + -2) Reorder the terms: -2x + 3x2 = (1 + 3x)(x + -2) Reorder the terms: -2x + 3x2 = (1 + 3x)(-2 + x) Multiply (1 + 3x) * (-2 + x) -2x + 3x2 = (1(-2 + x) + 3x * (-2 + x)) -2x + 3x2 = ((-2 * 1 + x * 1) + 3x * (-2 + x)) -2x + 3x2 = ((-2 + 1x) + 3x * (-2 + x)) -2x + 3x2 = (-2 + 1x + (-2 * 3x + x * 3x)) -2x + 3x2 = (-2 + 1x + (-6x + 3x2)) Combine like terms: 1x + -6x = -5x -2x + 3x2 = (-2 + -5x + 3x2) Add '-3x2' to each side of the equation. -2x + 3x2 + -3x2 = -2 + -5x + 3x2 + -3x2 Combine like terms: 3x2 + -3x2 = 0 -2x + 0 = -2 + -5x + 3x2 + -3x2 -2x = -2 + -5x + 3x2 + -3x2 Combine like terms: 3x2 + -3x2 = 0 -2x = -2 + -5x + 0 -2x = -2 + -5x Solving -2x = -2 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -2x + 5x = -2 + -5x + 5x Combine like terms: -2x + 5x = 3x 3x = -2 + -5x + 5x Combine like terms: -5x + 5x = 0 3x = -2 + 0 3x = -2 Divide each side by '3'. x = -0.6666666667 Simplifying x = -0.6666666667
| 1=0.99999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999 | | 0=0.000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000000 | | 1=1.1111111111111111111111111111111111111111111111111111111111111111111111111111111111 | | 5x^3+24x^2+16x=0 | | -20y-11-3=12 | | 70=2l+2w | | -9x=3x | | 0.10(117-x)+0.25x=15.75 | | m-99=299 | | 308=-28x | | (m+9)(m-3)= | | 0.1x-0.25x= | | 3x-5y+20=180 | | 36w^3-60w^2+9w= | | 3x+5y+10=180 | | X^2-10x+57=0 | | 2x-5-4=2 | | 4(t-3)+6t=5(2t+4)-9 | | 2v+12=-28 | | 3(4+5x)=-108 | | 8+15x=4+6x | | 6+18lnx=4 | | 12m^2+5m-2= | | sin^2x=2sinx+3 | | 2x^3-27000=0 | | x^2+13-114=0 | | 20=a | | 5x-32=2x+61 | | 7(-3-5x)=329 | | (w+2)(w-6)=0 | | 24a^2-9aq+16aq-6q^2= | | ln(ln^4x)=0 |